Do Islamic versus conventional banks progress or regress in productivity level? - Ribed Vianneca W. Jubilee; Fakarudin Kamarudin; Ahmed Razman Abdul Latiff; Hafezali Iqbal Hussain; Khar Mang Tan (Future Business Journal, 2021)
This study assesses the differences between Islamic and conventional bank's productivity. Earlier studies on bank productivity focused on conventional banks, but few have been done on Islamic banks. Therefore, the present study attempts to close the gap in the literature by investigating the productivity of Islamic and conventional banks in the context of the Middle East, Southeast Asia and South Asia regions. The sample is comprised of 385 banks (66 Islamic banks and 319 conventional banks) from 18 countries with data observations from 2008 to 2017. Panel data techniques with DEA-based MPI will be employed to investigate the impact of selected important factor and bank productivity as indicated by total factor productivity changes (TFPCH). Based on the results, Islamic banks are more productive than conventional banks and the results from t test are further confirmed by the results from nonparametric tests. These results are attributed to the progress in EFFCH. However, the mean difference between Islamic and conventional banks TFPCH is not statistically significant in all regions. The main benefit is that this work will hopefully provide additional insight and complement the existing studies on bank productivity of Islamic and conventional banks that are important to the banks, regulations, investors and researchers.
Keywords: G21; G28; 650; Conventional banks; Islamic bank; Malmquist productivity index; Middle East; South Asia; Southeast Asia; Total factor productivity change